Genetic polymorphism of pleiotrophin is associated with pain experience in Japanese adults: Case-control study. Issue 37 (16th September 2022) - Saita, Kosuke; Sumitani, Masahiko; Nishizawa, Daisuke; Tamura, Takashi; Ikeda, Kazutaka; Wakai, Kenji; Sudo, Yoshika; Abe, Hiroaki; Otonari, Jun; Ikezaki, Hiroaki; Takeuchi, Kenji; Hishida, Asahi; et al.
Abstract : Genetic factors play a role in individual differences in pain experience. Here, we performed a genome-wide association study (GWAS) to identify novel loci regulating pain processing. We conducted a 2-stage GWAS and the candidate single-nucleotide polymorphisms (SNPs) association study on pain experience using an exploratory cohort of patients with cancer pain. The confirmatory cohort comprised of participants from the general population with and without habitual use of analgesic medication. In the exploratory cohort, we evaluated pain intensity using a numerical rating scale, recorded daily opioid dosages, and calculated pain reduction rate. In the confirmatory cohort, pain experience was defined as habitual nonsteroidal anti-inflammatory drug usage. Using linear regression models, we identified candidate SNP in the exploratory samples, and tested the association between phenotype and experienced pain in the confirmatory samples. We found 1 novel SNP (rs11764598)—located on the gene encoding for pleiotrophin on chromosome 7—that passed the genome-wide suggestive significance at 20% false discovery rate (FDR) correction in the exploratory samples of patients with cancer pain ( P = 1.31 × 10 -7, FDR = 0.101). We confirmed its significant association with daily analgesic usage in the confirmatory cohort ( P = .028), although the minor allele affected pain experience in an opposite manner. We identified a novel genetic variant associated with pain experience. Further studies are required to validate the role of pleiotrophin in pain processing.